Biosurfactant as a preventive agent on acrylic resin (Mustansiria Dental Journal, 2019)
Objective. Current study was aimed to evaluate the activity of biosurfactants andother cleansing solutions of the acrylic resin on growth of Candida albicans andStreptococcus mutans.Study design. Heat cure acrylic resin discs were prepared and precoated with fourtypes of liquids: water, biosurfactant, chlorhexidine mouth wash and denturecleanser. The water was used as control. The discs kept in the solutions overnightafter that the antimicrobial assay was tested against Candida albicans andStreptococcus mutans. Also reduction of growth and biofilm formation of C.albicans on denture acrylic discs was tested by using biosurfactant.Results. Precoating with biosurfactant caused a greater inhibition in the growth ofboth types of the microorganisms than chlorhexidine and denture cleanser, withinhibition zone diameter 25mm and 15mm against Streptococcus mutans andCandida albicans respectively , 96 % of Candida albicans growth reduction ondenture acrylic discs. Also biosurfactant showed reduction in biofilm formation ofCandida albicans on denture acrylic discs.Conclusions. This study demonstrated that biosurfactant was the best preventiveagent for acrylic resin compared with other mouth washer and denture cleanser.